The Effectiveness of Na'o Beps Animation Video on Young Women's Knowledge and Skills in Early Detection of Breast Cancer by Breast Self-Examination (BSE) - Pombaile, Veny Delvia; Sutinah, Sutinah; Ahmad, Mardiana; Sinrang, Andi Wardihan; Nontji, Werna; Stang, Stang (JURNAL INFO KESEHATAN, 2023)
Breast cancer ranks first in cancer-related deaths in women in the world, which are generally found at an advanced stage. Breast self-examination (BSE) that has been used since puberty can detect breast cancer symptoms earlier so that treatment can achieve a survival probability of 90% or more. Animated video is one of the developments in health education media that is in line with advances in digital technology. This study aims to determine the effectiveness of the Na'o Beps animated video on improving the skills of young women in performing breast self-examination (BSE). This research is a research & development model of 4D development (define, design, develop, disseminate) and the research design used a pre-experimental design with a one-group pretest-posttest design. The sample in this study was all grade VIII students at SMP Negeri 14 Gorontalo City, Gorontalo Province in 2022, a total of 36 students. The sampling technique used purposive sampling. Data analysis in this study was carried out by the Wilcoxon test. The results showed that there were significant differences in the knowledge (p=0.00) and skills (p=0.000) of female adolescents regarding breast self-examination (BSE) after the intervention with the Na'o Beps animation video. Conclusion Health education using animated video media is effective in increasing the knowledge and skills of young women about breast self-examination (BSE) so that it can be used as an alternative medium in providing health education.